Knowledge, Attitude, and Practice of Primary School Teachers in Rafsanjan, Iran Regarding Emergency Events of Epilepsy and Asthma - Moslem Kohgardi; Mohammad Asadpour; Mostafa Nasirzadeh (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Qum, 2022)
Background and Objectives: Considering the prevalence of emergency events in schools and the key role of teachers in preventing and controlling these events, the present study aimed to determine the knowledge, attitude and practice of primary school teachers regarding emergency events related to epilepsy and asthma in Rafsanjan, Iran. Methods: This descriptive study was conducted on 101 primary school teachers in 2019-2020 who were selected by census sampling method. The data collection tool was a researcher-made questionnaire of knowledge, attitude and practice towards asthma and epilepsy and their subsequent emergencies. Data were analyzed in SPSS v.18 using Pearson correlation test, independent t-test and one-way ANOVA, considering the significance level at P<0.05. Results: Mean score of teachers’ knowledge, attitude and practice towards epilepsy were 77.9, 68.3, and 72.7 (out of 100), respectively; these scores towards asthma were 73.6, 81.5, and 71.6, respectively. There was a statistically significant correlation between the mean practice score of teachers in epilepsy with age (r= 0.221, P= 0.027) and level of education (F= 3.13, P= 0.029). Moreover, a significant relationship was observed between the mean knowledge score about asthma and educational level (F=2.85, P= 0.041), and between teachers’ practice in asthma and work experience (r = 0.303, P= 0.002). Conclusion: The design and implementation of educational and retraining interventions regarding epilepsy and asthma for younger teachers with lower work experience is suggested.